Effect of the recombinant chymosins of different origins on production process of soft cheese - D. S. Myagkonosov; I. T. Smykov; D. V. Abramov; I. N. Delitskaya; V. N. Krayushkina (Пищевые системы)
The effect of milk-clotting enzymes (MCE) with different milk-clotting activity (MCA) and proteolytic activity (PA) based on recombinant calf chymosins (Chy-max® Extra: MCA=554 IMCU/g; PA=0.71 UA/g), camel (Chymax® M: MCA=904 IMCU/g; PA=0.68 PA units/g) and “modified” chymosin (Chy-max® Supreme: MCA=912 IMCU/g; PA=0.26 PA units/g) on the duration of milk coagulation, the composition of whey and fresh cheeses in the production of soft cheese of the Italian type Crescenza at a dose of MCE equal to 1500, 2500 and 3500 IMCU per 100 kg of milk was studied. With an equal introduction dose, the shortest average duration of curd formation is noted for Chy-max Supreme MCE (15.0–27.5 min), long one — for Chy-max M MCE (17.0–31.0 min), and the longest one — for MCE Chy-max Extra (18.0–35.5 min). There was no statistically significant effect (p<0.05) of the type and dose of MCE on the total duration of cheese processing, as well as on the content of fat, protein and dry matter of whey. The type and dose of MCE had an impact on the properties of fresh cheeses: cheese options produced with the maximum dose of Chy-max Supreme had a statistically significant (p><0.05) higher average dry matter content (49.61%) than cheese options made with minimal doses of MCE (47.64–47.91%).>< 0.05) of the type and dose of MCE on the total duration of cheese processing, as well as on the content of fat, protein and dry matter of whey. The type and dose of MCE had an impact on the properties of fresh cheeses: cheese options produced with the maximum dose of Chy-max Supreme had a statistically significant (p<0.05) higher average dry matter content (49.61%) than cheese options made with minimal doses of MCE (47.64–47.91%).> <0.05) of the type and dose of MCE on the total duration of cheese processing, as well as on the content of fat, protein and dry matter of whey. The type and dose of MCE had an impact on the properties of fresh cheeses: cheese options produced with the maximum dose of Chy-max Supreme had a statistically significant (p<0.05) higher average dry matter content (49.61%) than cheese options made with minimal doses of MCE (47.64–47.91%).><0.05) higher average dry matter content (49.61%) than cheese options made with minimal doses of MCE (47.64–47.91%).